An early colonisation pathway into northwest Australia 70-60, 000 years ago. (15th January 2018) - Norman, Kasih; Inglis, Josha; Clarkson, Chris; Faith, J. Tyler; Shulmeister, James; Harris, Daniel
Abstract: Colonisation of Sahul 70-60 thousand years ago (kya) represents the first great maritime migration undertaken by anatomically modern humans in one of the final phases of the Out of Africa dispersal. Visual connectivity network analyses, agent-based simulations and ocean current modelling reveal that modern humans could follow numerous northern and southern migration pathways into Sahul. Our results support a southern route out of Africa through South Asia with entry into ISEA through the Banda Arc, culminating in an early colonisation of Sahul on the northwest shelf. Our results show multiple colonisation events through other entry points were also probable, and raise interesting possibilities for complex regional migration and population histories. Highlights: Network analysis demonstrates visual connectivity for northern and southern island migration routes from Sunda to Sahul. Agent-based simulations reveal multiple migration pathways to Sahul probabilistically likely. Current flow modelling highlights the southern pathway through Wallacea to Sahul.